Self-Organized Surface Structures with Ultrafast White-Light First Investigation of LIPSS with Supercontinuum - Uhlig, Sebastian; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2015)
Sebastian Uhlig presents the first experimental investigation of self-organized surface structures (LIPSS) generated by ablation from different (semiconductor and metallic) targets with an ultrafast white-light continuum (WLC) spreading in wavelength from 400-750 nm. The main goal is to study the possibility of LIPSS formation upon irradiation with an incoherent and polychromatic light source (e.g. the WLC) in order to discriminate between the two debated formation scenarios. The generation of a suitable WLC in terms of sufficient white-light pulse energy, broad spectral bandwidth, and low spatial coherence for the LIPSS generation, as well as the characterization of this WLC are additional important objectives of this work. Contents Introduction to Laser Induced Periodic Surface Structures (LIPSS) Introduction to White-Light Continuum Generation Characterization of White-Light Supercontinuum Self-Organized Pattern Formation with Ultrafast White-Light Target Groups Lecturers, researchers and students in the fields of Material Science, Microsystems, Engineering The Author Sebastian Uhlig studied physics at Brandenburg University of Technology Cottbus-Senftenberg and wrote his Master Thesis at the Chair of Experimental Physics II, under the supervision of Prof. Dr. Jürgen Reif. Currently, he is employed at the Fraunhofer Institute for Photonic Microsystems in Dresden, where he works on integrated sensors for a new class of electrostatic actuators.
Keywords: Physics; Continuum physics; Lasers; Photonics; Physics; Classical Continuum Physics; Laser Technology, Photonics; Electronic books